The Influence of Lifestyle and Fashion Interest on Impulse Buying Behavior on Tiktokshop - Lestari, Sephia Dewi; Fatmawati, Taffana Gita; Hernidatiatin, Lis Tatin (Devotion : Journal of Research and Community Service, 2024)
This study aims to test the variables of Fashion Lifestyle and Interest in Impulse Buying Behavior on TiktokShop Erigo Products for Wiilayah Ciayumajakuning. Using a type of quantitative approach research method and research population, namely Erigo Product Consumers on TiktokShop for the Ciayumajakuning Region with a total of 97 respondents. This Sample Collection Technique uses Non-Probability Sampling. Data Collection Techniques using Questionnaires and data analysis used are multiple regression analysis, and data analysis techniques using SPSS Program version 27. Obtained results that show that Lifestyle on Impulse Buying Behavior does not have a significant influence while Fashion Interest on Impulse Buying Behavior has a significant influence, Lifestyle and Fashion Interest  simultaneously on Impulse Buying Behavior have a significant influence.